2014
DOI: 10.5812/ircmj.18371
|View full text |Cite
|
Sign up to set email alerts
|

Aromatherapy With Citrus Aurantium Oil and Anxiety During the First Stage of Labor

Abstract: Background:Anxiety is the most common psychological response of women to labor. Aromatherapy, i.e. the use of fragrant essential oils to stimulate the olfactory system, can create a state of calmness and help to alleviate anxiety.Objectives:The present study tried to determine the efficacy of aromatherapy with Citrus aurantium oil in reducing anxiety during the first stage of labor.Patients and Methods:This randomized clinical trial was conducted on two groups of pregnant women, referred to Vali-Asr Hospital (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0
16

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 21 publications
4
66
0
16
Order By: Relevance
“…A recently conducted double-blinded, randomized, controlled clinical trial study on aromatherapy has suggested that citrus oil is good in relieving the first stage labor pain. It is effective in controlling the nausea and vomiting along with its mood elevating properties [58][59][60] .…”
Section: Lemonmentioning
confidence: 99%
“…A recently conducted double-blinded, randomized, controlled clinical trial study on aromatherapy has suggested that citrus oil is good in relieving the first stage labor pain. It is effective in controlling the nausea and vomiting along with its mood elevating properties [58][59][60] .…”
Section: Lemonmentioning
confidence: 99%
“…amara and other Citrus species, is rich in limonene and linalool [4]. It has been widely used in humans for managing anxiety and stress because of its relaxing effect, for instance during labor [5]. A recent cardiovascular study also reported that neroli essential oil reduced blood pressure in humans [6].…”
Section: Introductionmentioning
confidence: 98%
“…Lime oil is a pale yellow or green liquid. It stimulates the central nervous system, enhances the mood, lowers blood pressure, and has sedative, analgesic, antiinflammatory, antispasmodic, carminative, digestive, and diuretic effects [3]. Pine oil is a colorless or pale yellow liquid with strong, dry-balsamic, turpentine-like aroma.…”
mentioning
confidence: 99%